Practical guide to studying history skills and approaches - Loughran, Tracey (London ; New York Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc, 2017)
"An introduction to the fundamental skills and principles underpinning historical research and writing, and to the different contexts in which history is produced and consumed"-- Provided by publisher.
Machine generated contents note: -- List of Illustrations -- Introduction - Tracey Loughran (Cardiff University, UK) -- Part I: Framing Histories -- Introduction: Frameworks and Perspectives / Tracey Loughran (Cardiff University, UK) -- 1. Nations / Mark Williams (Cardiff University, UK) -- 2. Periodization / Shaun Tougher (Cardiff University, UK) -- 3. Comparative Histories / Chiara Beccalossi (University of Lincoln, UK) -- 4. Biography / Toby Thacker (Cardiff University, UK) -- 5. People's History / Martin Wright (Cardiff University, UK) -- 6. Identities / Siobhan McGurk (University of Wisconsin-Madison, USA) -- Part II: The Historian's Craft -- Introduction / Tracey Loughran (Cardiff University, UK) -- 7. Historical Research / Garthine Walker (Cardiff University, UK) -- 8. Evidence and Interpretation / Kevin Passmore (Cardiff University, UK) -- 9. Archives / Federica Ferlanti (Cardiff University, UK) -- 10. Documents, Editions and Translations - Helen J. Nicholson (Cardiff University, UK) -- 11. The Good, the Bad, and the Ugly: Sources for Essays - Keir Waddington (Cardiff University, UK) -- 12. Reading and Writing History / Tracey Loughran (Cardiff University, UK) -- Part III: History in Public -- Introduction / Tracey Loughran (Cardiff University, UK) -- 13. History in Schools / Lloyd Bowen (Cardiff University, UK) -- 14. History and Policy / Matthew Grant (University of Essex, UK) -- 15. Historical Novels / Tracey Loughran (Cardiff University, UK) -- 16. History and Heritage / Stephanie Ward (Cardiff University, UK) -- 17. Exhibiting History / Jane Hamlett (Royal Holloway, University of London, UK) -- 18. Taking History into the World / Dave Wyatt (Cardiff University, UK) -- Index.
Includes bibliographical references and index.
Keywords: History -- Study and teaching; History -- Methodology; History -- Research; Historiography; Public history